Characterization of human papillomavirus (HPV) 16 E6 seropositive individuals without HPV-associated malignancies after 10 years of follow-up in the UK Biobank - Brenner, Nicole (EBioMedicine, 2020)
BACKGROUND: Antibodies against the HPV16 oncoprotein E6 are promising biomarkers for HPV16-driven oropharyngeal cancer (HPV16-OPC) due to their high sensitivity and specificity, and prospective manifestation. In previous studies, 0•7% of controls without HPV-associated malignancies were HPV16 E6 seropositive of which only a minority is expected to develop HPV16-driven cancer. We aimed to characterise HPV16 E6 antibodies in individuals without HPV-associated malignancies. METHODS: We analysed serum antibodies against HPV16 E6, E7, L1 and HPV18 L1 in a random sample (n = 9,695) of the prospective UK Biobank cohort (UKB). Excluding individuals with potentially HPV-associated malignancies (n = 192), we assessed risk factors for seropositivity by logistic regression. FINDINGS: In individuals without potentially HPV-associated malignancies (n = 9,503), the HPV16 E6 seroprevalence was 0•8%. Seropositivity against HPV16 E6 and all other HPV antigens was strongly associated with sexual behaviour. The seroprevalence of HPV16 E6, L1 and HPV18 L1 increased with the number of lifetime sex partners (p(trend)<0•005), and all HPV antibodies were associated with same-sex intercourse (OR(E6) 3•1, 95%CI 1•4–6•9; reference category: no same-sex intercourse). HPV16 E6 and L1 seropositivity were associated with young age (≤17 years) at sexual debut (OR(E6) 2•0, 95%CI 1•1–3•7) compared with individuals reporting sexual debut at age ≥20 years. INTERPRETATION: This is the first study characterising HPV16 E6 antibodies in the general UK population. Their strong association with sexual behaviour, and overlapping risk factor profiles with other HPV antibodies support their relevance for HPV16-OPC disease prediction. However, additional risk stratification will be required to identify individuals at highest risk to develop HPV16-OPC.